2023
DOI: 10.1186/s43044-023-00400-2
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on post-discharge venous thromboembolism prophylaxis in patients with COVID-19

Reza Amani-Beni,
Mohammad Kermani-Alghoraishi,
Bahar Darouei
et al.

Abstract: Background Coronavirus disease of 2019 (COVID-19) is associated with venous thromboembolism (VTE), not only during hospitalization but also after discharge, raising concerns about anticoagulant (AC) use for post-discharge COVID-19 patients. We aimed to systematically review the current literature on the possible benefits or risks regarding extended thromboprophylaxis. Main body We searched related databases from December 1, 2019, to October 6, 2022… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The ACTIV-4c trial results are similar to incidence of thrombosis seen in similar patient cohorts. Several meta-analyses have summarized postdischarge arterial and venous thrombosis over the course of the pandemic [ [15] , [16] , [17] ]. The first meta-analysis of 11 studies showed a cumulative postdischarge pooled incidence of VTE of 1.8% [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ACTIV-4c trial results are similar to incidence of thrombosis seen in similar patient cohorts. Several meta-analyses have summarized postdischarge arterial and venous thrombosis over the course of the pandemic [ [15] , [16] , [17] ]. The first meta-analysis of 11 studies showed a cumulative postdischarge pooled incidence of VTE of 1.8% [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given this situation, the diagnosis of clinical and laboratory criteria for thrombotic risk stratification is a priority for clinical trials to optimize thromboprophylaxis [15].…”
Section: Introductionmentioning
confidence: 99%